The lion and the fox: an animal metaphor for two laudandi in Pindar - Pitotto, Elisabetta (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2023)
The lion and the fox: an Animal Metaphor for two laudandi in Pindar focuses on the communicative functions of the references to the couple formed by the lion and the fox in Pindar’s Olympian XI and Isthmian IV. The first part of this article considers the qualities traditionally associated to the fox and the lion in archaic epic and lyric diction. Set against this background, the two metaphors -to which Pindar recurs when it comes to praise Hagesidamos and Melissos respectively- become more meaningful. Used in the key moments of the two epinicians, they help performing two important tasks: painting a suitably encomiastic portrait of the patrons; facing the overall socio-political issues reflected in each song.